Breast cancer in 80+ year olds - Kosáč, P; Zábojníková, M; Vážan, P; Petrů, V; Ratajský, M; Lajmar, K; Dudešek, B; Kudlová, P; Duben, J; Podrazká, L; Gatěk, J (Rozhledy v chirurgii, 2024)
INTRODUCTION: The risk of breast cancer increases with increasing age. The aim of our retrospective study was to determine the extent of breast and axillary surgery, including subsequent adjuvant therapy, in 80-year and older patients. METHODS: Between 2017 and 2021, 834 breast cancer patients were operated in the Surgical Department of the EUC Clinic. Ninety-eight women (2× with bilateral cancer) and 2 men were included in this retrospective study. A total of 102 breast cancer cases in patients older than 80 years were analyzed. The surgical procedure corresponded to the stage of the disease and the general condition of the patient. Adjuvant systemic therapy was indicated according to the same principles. RESULTS: At the time of surgery, the patients were more than 80 years old (80-96 years). The predominant type of invasive ductal carcinoma was diagnosed 83×, lobular carcinoma 6×, mucinous 6×, papillary carcinoma 4×, other 3×, with luminal A, B predominating (89×). The breast-conserving procedures were performed 63×. Sentinel node biopsy was performed 65×, supplemented by axillary lymph node dissection 13×. Primary axillary lymph node dissection was performed 15×. No axillary procedure was performed 23×. Radiotherapy was given 49×, chemotherapy 9× and hormonal therapy 82×. Local and regional recurrences were each observed 2×. A total of 37 patients died, 10 of them from breast cancer. CONCLUSION: The most common cause of death in patients aged 80+ years is a cardiovascular disease, not breast cancer itself. This fact should be taken into account when determining the treatment plan.
Keywords: nádory prsu u mužů; Sentinel Lymph Node Biopsy; senioři nad 80 let; Axilla; surgical therapy; nádory prsu; retrospektivní studie; Humans; adjuvantní radioterapie; lymfadenektomie; Carcinoma, Ductal, Breast; Aged, 80 and over; breast cancer; Breast Neoplasms; Radiotherapy, Adjuvant; Chemotherapy, Adjuvant; mužské pohlaví; duktální karcinom prsu; surgical treatment; segmentální mastektomie; axila; Mastectomy, Segmental; ženské pohlaví; Lymph Node Excision; lidé; 80 years; adjuvantní chemoterapie; Breast Neoplasms, Male; biopsie sentinelové lymfatické uzliny; Retrospective Studies; Male; Female